Molecular Docking of Cocculus hirsutus Phytocompounds with the Selective DENV Virus Stereotypes - Prabhuram K; Shubham Wanarase (International Journal of Genetic Modifications and Recombinations, 2023)
Dengue is a tropical disease with a high infection rate worldwide. Though treatments are available for the symptoms, anti-dengue drugs are unavailable. To tackle this issue, the study aims to shortlist the potential phytocompounds from Cocculus hirsutus medicinal plant, prevalent in South and South East Asia. Using molecular docking and ADME analysis, two potential compounds possessing high drug-likeness are identified namely, Sinococuline and Morphinan.
Keywords: DENV; NS1; anti-dengue; molecular docking